The Diminished Importance of Cultural Sustainability in Spatial Planning: The Case of Slovenia - Ursic, Matjaz (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
Formal spatial planning procedures tend to neglect the importance of socio-cultural elements that are inherently present as part of 'soft infrastructure' and are constituted from traditions, lifestyles, wishes, and the routines of individuals that form a local community. In contrast, the concept of cultural sustainability is closely linked with the socio-cultural heterogeneity of a local community. The inability of the formal spatial planning system in Slovenia to adequately engage with the social wishes and resistances of residents is highlighted in situations involving problematic confrontations between the members of the dominant 'common culture' and marginal groups. Two cases from Ljubljana are presented: the stigmatization of the Fužine neighbourhood and the problematic of mosque construction. The cases illustrate that the 'majority' of residents tend to perceive many subcultural representations in space as foreign, non-indigenous elements that could disrupt the everyday routine in a local community. They show how the deficiencies of the current spatial planning system in Slovenia are unable to address challenges posed by contemporary society's cultural, social, and economic transformations and can work quite the opposite way – by increasing the complexity (and level of difficulty) for possible implementation of measures supporting cultural heterogeneity in planning practice.